Community Health Agents and child health care: implications for continuing education - Vieira, Caroline Lopes; Silva, Valentina Barbosa da; Parmejiani, Elen Petean; Cavalcante, Daniela Ferreira Borba; Souza, Maria Helena do Nascimento; Stipp, Marluci Andrade Conceição (Revista da Escola de Enfermagem da USP, 2022)
Objective: To understand the main situations faced by community health agents in relation to children’s health in the light of permanent education actions. Method: This is a research of qualitative approach, which used the Arc of Maguerez. Ten community health agents from a Primary Health Care Unit participated in the study. The following steps were addressed: observation of reality; identification of key points, and theorization. The speeches were recorded, transcribed, and their textual content was processed in the IRAMUTEQ software, using the Descending Hierarchical Classification. Results: Five classes were formed, which composed three thematic blocks named as follows: child’s social vulnerability in the territory; handling the child’s health record, and vaccination schedule. Conclusion: Unveiling situations that influence the work of community health agents is essential for continuing education, as this favors assumptions applicable to daily work with resoluteness in child health.